Yarsagumba collection and marketing: A key income source of people in Api Nampa conservation area, Darchula, Nepal - Karki, Renuka; Kandel, Khagendra; Kunwar, Aashish; Bhatta, Jagdish; Panthi, Shambhu; Pant, Prakash Kumar (Journal of Agriculture and Natural Resources, 2020)
Yarsagumba the Himalayan gold rush is the major part of the economy of the himalayan people in the Darchula distict. Our study was conducted in Khandeshwori region of the the Darchula district to quantify the contribution of Yarsagumba on the total household income of the harvester and to reveal the problems releated to its harvesting and selling. Income from Yarshagumba accounted upto 68% in this region. Geo-physical problems were observed most during collection along with significant conflicts and lower productivity. Price variation is the major market problem of those Yarshagumba harvesting peoples. Social factors like family size, adult members and educational factors have significant impact in total collection and income. The highest price obtained was Rs.18408.33, average price was Rs.15308.33 and the lowest price was Rs. 10205. Benefit to cost or expenses (BC) ratio found in research area was 5.13. Having sharp eye vision school children were taken for the collection and have to leave school for time. Although the data is emerging on medicinal use and market of Yarshagumba little systematic research has explored village level harvesting practice and socioeconomic impacts, especially in this region of Nepal.